ANALISIS HUBUNGAN POLITIK DAN DUKUNGAN ORGANISASIONAL DENGAN SIKAP KERJA, KINERJA, DAN PERILAKU CITIZENSHIP ORGANISASIONAL - Fenika Wulani (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2004)
This study examined relationship of organizational politics and support to job satisfaction, turnover intent, organizational commitment (affective dan normative), job performance and OCB; and to investigated whether politics could explained incremental variance in dependent variable beyond be explained by support, or vice versa. The sample was accountant staff those working at 15 Public Accountant Offices in Surabaya.The result show that politics were negatively related to job satisfaction, affective and normative commitment, job performance; positively related to turnover intent. Support was positively related to job satisfaction, affective and normative commitment; negatively related to turnover intent. Politics and support could explained incremental variance beyond each other.Keywords: organizational politics, job performance, politics support